Women's Struggle For Equality In Sidney Sheldon's Bloodline:A Feminist Approach - Sulistyowati, Ira (2004)
The major problem of this study is how women's struggle for equality is reflected in Sidney Sheldon's Bloodline. Meanwhile, this problem is limited on the major character, especially Elizabeth Roffe. In addition, the writer also limits the Feminist perspective on the Liberal Feminism. The objectives of this study are to analyze the novel based on its structural elements, and on the Feminist Approach, especially the Liberal Feminism. This Research Paper belongs to qualitative study that uses two data sources, primary data source and secondary data source. Primary data source in the novel itself and secondary data source is taken from different references that include; the material about Feminist literary theory, the books about Feminist approach especially equality theory, and some articles from Internet related to the study. The method of data collecting is library research, and technique of analysis is descriptive analysis. The outcome of the study shows the following conclusion. First, the study shows that there is a close relationship between literature and the social reality where the work was produced. Second, Sheldon's Bloodline represents his response to the twentieth century American society, particularly the problem of gender equality. Third, Sheldon wants to assert that women should be equal to men in position, role, right, and participation.